"In Safe Hands" – A costly integrated care program with limited benefits in stroke unit care. (January 2019) - Jala, Sheila; Giaccari, Sarah; Passer, Melissa; Bertmar, Carin; Day, Susan; Griffith, Dayna; Krause, Martin
Highlights: SIBR did not affect stroke patients' length of stay and incidence of adverse events. No benefits of SIBR in a stroke unit with regards to patient and staff satisfaction. Limited gains of implementing costly SIBR in a well organised unit. Abstract: Given reported favourable outcomes of accountable care unit models of health care delivery (Taylor et al., 2017; Stein et al., 2015; Kara et al., 2015), the Clinical Excellence Commission of NSW has embraced "In Safe Hands" (ISH) to enhance coordination of care. ISH embraces the structured interdisciplinary bedside round (SIBR) component, for which reported outcomes include reduced length of stay (Taylor et al., 2017; Stein et al., 2015; Kara et al., 2015), possible reduction in overall costs of care (Kara et al., 2015), and enhanced patient and staff satisfaction (O'Leary et al., 2011). It is not yet clear whether the benefits of such a model are translatable to the Australian Health Care System (Hunyh et al., 2016) and/or established units with an already strong multi-disciplinary approach to patient care. The purpose of this prospective cohort study of 200 participants was to assess the effect(s) of implementation of ISH in a stroke unit of a tertiary hospital in Sydney, Australia. Data on length of stay, re-admission rates, adverse events, as well as patient and nursing satisfaction, were collected pre and post implementation. There was no significant difference in length of stay in median days (5 (IQR 2–7) versus 4 (IQR 2–6), P = 0.55) or incidence of adverse events (10% versus 12%, P = 0.82). Stroke outcome disability scores were not affected by the intervention. There were no significant differences overall in reported patient and nursing satisfaction. Implementation of the ISH program cost approximately AUD 1805/week (USD 1365) in wages. The ISH program was a costly intervention of limited benefit in a well-established acute stroke unit. We here discuss potential reasons for the failure of this intervention to achieve its primary aim in this setting.